Profil Eosinofil Sapi Sumba Ongole yang Diberikan Pakan Tepung Kelor (Moringa oleifera Lam.) - Datta, Frans Umbu; Kaka, Fautinus Mone; Detha, Annytha Ina Rohi; Ndaong, Nemay; Foeh, Nancy (JURNAL KAJIAN VETERINER, 2021)
Moringa oleifera Lam contains protein compounds, vitamin A, minerals, essential amino acids, antioxidants, and flavonoids, and has an impact on the hematological profile. Based on the evaluated phytochemical, The aim of this study was to identify the eosinophil image of Sumba Onggle Cattle fed with moringa. The research was started from March to September 2017. The research was carried out was in the Integrated Dry Land Laboratory, Nusa Cendana University. and Regional Health Laboratory of East Nusa Tenggara Province. The stages of the research were started with the selection of the sample of the studied cattle (12 adult Sumba Ongole Cattle), the adaptation period, and the duration of treatment of moringa on the cattle for 50 days. The research sample chosen was. The results of the research data showed that the value of eosinophil in the first treatment from 0.32 x 103 / µl to 0.47 x 103 / µl. In contrast to treatment 2 which has a range of eosinophils at a value of 0.04 x 103 / µl to 0.69 x 103 / µl. However, the eosinophil value at the end of the treatment was in the normal range in cattle (0.1 x 103 / µl-1,2x 103 / µl). Eosinophil value data on day 50 showed that eosinophil values tended to increase and in the normal range of eosinophils. These results indicate that the cows fed with moringa showed an eosinophil profile that remained in the normal range.